Pengaruh elisitasi terhadap pertumbuhan dan produksi alkaloida kinolin dari akar rambut tanaman kina (Cinchona succirubra Pavon ex Klotzsch) Effect of elicitation on growth and alkaloid quinoline production in hairy root of cinchona plant (Cinchona succirubra Pavon ex Klotzsch) - Nurita TORUAN-MATHIUS; . NURHAIMI-HARIS; Joko SANTOSO; . ADE-HERI (E-Journal Menara Perkebunan, 2006)
Summary Manipulation to increase alkaloid producti-vity in hairy root  can be done by elicitation with the addition of certain  enzymes. The objective of  this research is to find out the effect of elicitation by cellulase and pectyoliase enzymes on the productivity of Cinchona succirubra  hairy root culture. Hairy root was  cultured on ½ MS macro nutrient with the addition of 40 g/L sucrose and  7 g/L agar. Elicitation was done by the addition of cellulase and pectiolyase at the concentrations of 0; 0.05; 0.10; 0.50; 1.00; 3.00; 5.00; 10.00; 15.00; 20.00 and 25.00 mg/L, respectively.The effect of elicitation was  analyzed by fresh weight of hairy root, and alkaloid content in four-month-old culture.The result showed that the best growth was obtained by the addition of 15 mg/L cellulase, with fresh weight as much as  920 mg. The addition of 10 mg/L pectyoliase increased  hairy root fresh weight as much as  880 mg. The highest quinoline alkaloid production was obtained by the addition of 25 mg/L celluase (Quinine 580, quinidine 492, cinchonine 234, dihydroxyn-chonine 195 and cinchonidine 165 µg/g fresh weight) and 1 mg/L pectyoliase (Quinine 2363, quinidine 238, cinchonine 104, dihydroxyn-chonidine 138 and cinchonidine 1558 µg/g fresh weight).Ringkasan Manipulasi untuk meningkatkan produk-tivitas  akar rambut  dapat dilakukan di antaranya dengan elisitasi melalui penambahan enzim tertentu ke dalam medium. Tujuan penelitian ini adalah untuk menetapkan pengaruh elisitasi dengan penambahan selulase dan pektioliase terhadap produktivitas akar rambut tanaman Cinchona succirubra. Akar rambut tanaman Cinchona succirubradikulturkan dalam medium MS ½ hara makro dengan penambahan sukrose 40 g/L dan agar 7 g/L. Elisitasi dilakukan dengan penambahan selulase dan pektioliase  masing-masing pada konsentrasi 0; 0,05; 0,10; 0,50; 1,00; 3,00; 5,00; 10,00; 15,00; 20,00 dan 25,00 mg/L. Peubah yang diukur adalah bobot basah akar rambut dan kandungan alkaloida kinolin pada kultur berumur empat bulan. Hasil yang diperoleh menunjukkan bahwa pertumbuh-an terbaik terjadi pada  penambahan konsentrasi selulase 15 mg/L  dengan bobot basah 920 mg dan pektioliase  10 mg/L dengan bobot basah   880 mg. Produksi alkaloida kinolin tertinggi  diperoleh   pada   konsentrasi   selulase  25 mg/L (kinin 580, kinidin 492, sinkonin 234, dihidrok-sinkonin 195 dan sinkonidin 165 µg/g bobot basah) dan pektioliase 1 mg/L (kinin 2363, kinidin 238, sinkonin 104, dihidroksinkonin 138 dan sinkonidin 1558 µg/g bobot basah).